Interest of Class X Students to Participate in Extracurricular Activities of SMA Negeri 1 Waway Karya - Rahmadani, Naufal Huda; Wicaksono, Lungit; Sumantri, Riyan Jaya; Siswoyo, Joan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Extracurricular activities have an important role in developing students' potential as a whole, both from cognitive, social, and character aspects. However, differences in social conditions, facilities, and policies between schools often lead to variations in student participation rates. This study aims to describe the level of interest of class X students in participating in extracurricular activities at SMA Negeri 1 Waway Karya and analyze the intrinsic and extrinsic factors that affect it. This study involved all 216 students of class X as participants with a total sampling technique. The method used is descriptive quantitative with a survey approach. The research instrument was a four-choice Likert scale closed questionnaire, which was tested for validity and reliability with very high results (r₁₁ = 0.891). The data was analyzed using a percentage descriptive technique to illustrate the tendency of students' interest in each indicator. The results showed that the overall level of student interest was in the very high category (79%), with an intrinsic factor of 80% and an extrinsic factor of 76%. The most in-demand extracurricular activity is volleyball (23%), while the least popular is vocal arts (0%). It was concluded that encouragement from within students was more dominant in influencing participation than environmental factors. This research contributes to providing empirical data for schools to develop more effective extracurricular coaching policies and strategies and becomes the basis for further research related to student motivation and performance in non-academic activities.